2017
DOI: 10.1007/s11948-017-9987-y
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Ethical Climate and Research Pressures in Different Faculties of a University: Cross-Sectional Study at the University of Split, Croatia

Abstract: We determined the prevailing ethical climate at three different schools of a single university, in order to explore possible differences in the ethical climate related to different research fields: the School of Electrical Engineering, Mechanical Engineering, and Naval Architecture; the School of Humanities and Social Sciences; and the School of Medicine. We used the Ethical Climate Questionnaire to survey the staff (teachers and administration) at the three schools, and used the research integrity and organiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 42 publications
(87 reference statements)
0
5
0
1
Order By: Relevance
“…Our recent study, which identified that the University of Split School of Medicine has an ethical climate predominantly driven by self-interest (Malički et al 2017), supports, at least in part, the relationship of the institutional climate and the perception of research misconduct. Overall, the ethical climate at the University of Split was rules-based, which can be expected in a system where, until recently, all schools were public schools and have to comply to national regulations in all aspects of academic work (Malički et al 2017). When the overall environment in a small postcommunist country is open to cheating (Kukolja Taradi et al 2010), it is not surprising that these culture-related behaviors influence the perception of research misconduct in academic institutions.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Our recent study, which identified that the University of Split School of Medicine has an ethical climate predominantly driven by self-interest (Malički et al 2017), supports, at least in part, the relationship of the institutional climate and the perception of research misconduct. Overall, the ethical climate at the University of Split was rules-based, which can be expected in a system where, until recently, all schools were public schools and have to comply to national regulations in all aspects of academic work (Malički et al 2017). When the overall environment in a small postcommunist country is open to cheating (Kukolja Taradi et al 2010), it is not surprising that these culture-related behaviors influence the perception of research misconduct in academic institutions.…”
Section: Discussionmentioning
confidence: 55%
“…Ethical climate in an institution has shown to be predictive of research misconduct (Pupovac and Fanelli 2015). Our recent study, which identified that the University of Split School of Medicine has an ethical climate predominantly driven by self-interest (Malički et al 2017), supports, at least in part, the relationship of the institutional climate and the perception of research misconduct. Overall, the ethical climate at the University of Split was rules-based, which can be expected in a system where, until recently, all schools were public schools and have to comply to national regulations in all aspects of academic work (Malički et al 2017).…”
Section: Discussionmentioning
confidence: 67%
“…In the category (IR Environment), studies conducted during 2019, 2020 and 2022 show barriers not conducive to a responsible research environment such as: lack of support from research institutions due to excessive bureaucracy, unfair evaluation policies, overwork, insufficient supervision of researchers, and little commitment to address integrity (Haven et al, 2019(Haven et al, , 2020. Furthermore, individual, group, or organizational pressures on horship or co-authorship and questionable research practices are appreciated in their environment (Hofmann & Holm, 2019;Malički et al, 2019), pressure to engage in commissioned or externally funded research that may have positive or negative effects, pressure to publish more without sacrificing quality (Kennedy et al, 2023;Vie, 2022). From 2014 to 2018, 2021 no publications on the subject.…”
Section: Resultsmentioning
confidence: 99%
“…They also perceived the most favourable ethical climate in laws and professional codes, and the most negative ethical climate was in efficiency and benevolence (Ekinci 2017). A study conducted in various faculties of a university in Croatia found that laws and professional codes was dominant in general, that a climate of self-interest was more dominant in the medical faculty and that friendship was the most negatively perceived type of ethical climate (Malicˇki et al 2019). A study performed with academics in the Philippines reported that their perceptions on social responsibility and company rules and procedures were more positive, and the most negative perception was in the climate of friendship (Monteagudo 2016).…”
Section: Discussionmentioning
confidence: 99%